"Food addiction is real". The effects of exposure to this message on self-diagnosed food addiction and eating behaviour. (1st August 2015) - Hardman, Charlotte A.; Rogers, Peter J.; Dallas, Rebecca; Scott, Jade; Ruddock, Helen K.; Robinson, Eric
Highlights: The effects of food addiction messages on self-diagnosis and intake were examined. Bogus news articles were used which claimed that food addiction is real or a myth. Self-diagnosis was higher in the Real condition relative to the Myth condition. Intake of indulgent foods in a taste test was more variable in the Real condition. Abstract: Food addiction is widely discussed in popular media in many Westernised societies. However, a potential concern is that endorsement of the food addiction model may cause people to perceive a lack of personal control over eating which could promote unhealthy dietary behaviours. To address this possibility, the current study investigated whether exposure to food addiction messages would, firstly, increase the number of participants who self-diagnosed as food addicts and, secondly, increase intake of indulgent foods. In a between-subjects design, participants ( N  = 60) read an article which either claimed that food addiction is real ("Real" condition) or that food addiction is a myth ("Myth" condition). Intake of indulgent and non-indulgent foods was then assessed in a disguised taste test and participants also completed a measure of self-diagnosed food addiction. A significantly higher proportion of participants in the Real condition self-diagnosed as food addicts relative to participants in the Myth condition (57% and 27% of participants, respectively; p  = .018). Variability in intake, but not mean intake, of indulgent food was higher in the Real condition than in the Myth condition. These findings suggest that endorsement of the concept of food addiction may encourage people to self-diagnose as food addicts and thus explain their eating behaviour in terms of addiction (an external attribution). The extent to which self-diagnosis of food addiction influences actual food intake and how this might vary with individual differences and eating context remains to be determined.